2020
DOI: 10.1111/hsc.13014
|View full text |Cite
|
Sign up to set email alerts
|

Death, loss and community—Perspectives from children, their parents and older adults on intergenerational community‐based arts initiatives in Sweden

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
1
21
0
3
Order By: Relevance
“…In our data we could identify a Studio DöBra magic circle, i.e., the spatial and temporal boundaries of the arts workshops. Additionally, in line with Huizinga, the norms and customs inside the Studio DöBra magic circle deviated from ordinary life in that participants and partners interacted across generations beyond their families and engaged with EoL issues, whereas this would not occur in ordinary life in the same way, as indicated by our previous research [ 4 , 5 ]. However, participants and partners appeared to move in and out of playful modes within the Studio DöBra magic circle, rather than Huizinga’s idea of a magic circle as a separation between play and ordinary life, or Frissen et al’s ideas about play and ordinary life occurring simultaneously.…”
Section: Methodssupporting
confidence: 61%
See 4 more Smart Citations
“…In our data we could identify a Studio DöBra magic circle, i.e., the spatial and temporal boundaries of the arts workshops. Additionally, in line with Huizinga, the norms and customs inside the Studio DöBra magic circle deviated from ordinary life in that participants and partners interacted across generations beyond their families and engaged with EoL issues, whereas this would not occur in ordinary life in the same way, as indicated by our previous research [ 4 , 5 ]. However, participants and partners appeared to move in and out of playful modes within the Studio DöBra magic circle, rather than Huizinga’s idea of a magic circle as a separation between play and ordinary life, or Frissen et al’s ideas about play and ordinary life occurring simultaneously.…”
Section: Methodssupporting
confidence: 61%
“…Within this, partners and participants sometimes used their imagination to engage with EoL issues, and sometimes introduced elements from ordinary life by sharing EoL-related experiences, such as the death of a family member or a pet. Additionally, our earlier analyses indicated that participants created spaces in their social networks for engaging with EoL issues stimulated through Studio DöBra participation [ 4 ]. We therefore conceptualize the Studio DöBra magic circle as a permeable boundary through which participants could introduce experiences from ordinary life into Studio DöBra and introduce elements from Studio DöBra into their ordinary lives, as illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations